Pelatihan Manajemen Diri Pasien Hipertensi Dengan Pendekatan Health Belief Model - I Nyoman Purnawan; Ni Wayan Putri Larassita; Ni Komang Sriwisani S (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Denpasar City, the prevalence of hypertension and its related complications increased by 2.14% between 2023 and 2024. The incidence of complications among hypertensive patients is largely attributed to poor self-management. This community service program (PKM) aimed to enhance the knowledge and self-management behaviors of hypertensive patients through the application of the Health Belief Model approach. The program was implemented at Puskesmas I West Denpasar in October 2025 and consisted of health education sessions and progressive muscle relaxation exercise training for 25 Prolanis participants. The program produced two main outputs: a self-management guidebook and an educational video for hypertensive patients. Among the 25 participants, the mean knowledge score increased from 6.30 (pretest) to 9.40 (post test), indicating an improvement of 3.10 points. The mean score for relaxation exercise behavior increased from 6.10 to 9.50, reflecting an improvement of 3.40 points. Meanwhile, the mean blood pressure decreased from 150/95 mmHg to 138/88 mmHg, showing a reduction of 12/7 mmHg. These findings demonstrate that the intervention effectively improved participants’ knowledge and self-management behavior, accompanied by a significant reduction in blood pressure. It is recommended that similar community service programs be implemented more comprehensively by involving various related sectors, particularly with the support of health workers in providing relaxation exercise training for hypertension patients.